The Not-So-Sweet Side of Diabetespictorial Review of the Most Frequent Diabetic Foot Disorders [el Lado Menos Dulce de la Diabetes. Revisión Pictográfica de Las Alteraciones Más Frecuentes en el Pie Diabético] - Jara-Munoz, P (Georg Thieme Verlag, 2021)
The global prevalence of Diabetes Mellitus (DM) tends to increase over the years, along with its complications. Diabetes related foot disease has become one of the leading causes of morbidity and disability. The most frequent findings are skin and muscle disorders, arteriosclerosis and bone marrow edema. Complications are osteomyelitis and neuroarthropathy, being important causes of amputation. The imaging study begins with radiography, which allows to rule out bone and joint abnormalities, presence of foreign bodies or soft tissue alterations. After radiography, magnetic resonance imaging (MRI) is the chosen modality to study osteomyelitis and soft tissue infection of the foot. Although these conditions share some clinical and imaging characteristics with other disorders, to know the distinctive findings allows the radiologist to contribute to get a timely and correct diagnosis, providing as well an appropriate information to the clinician. © 2021 Georg Thieme Verlag. All rights reserved.